Analysis of Factors Influencing Purchase Intentions in Live Shopping in Batam - Chrisderry; Christiarini, Renny (Paradoks : Jurnal Ilmu Ekonomi, 2025)
Purpose: This research aims to analyze the influence of argument quality, credibility of influencers and interactivity, kindness on consumer welfare and purchase intentions on live shopping broadcast from Batam. Methodology/Approach: The research approach is quantitative, by obtaining data through distributing questionnaires to 200 livestreaming shopping users in Batam City. Data analysis through the SMART-PLS statistical program, by carrying out validity, reliability tests, direct influence tests via path coefficients, coefficient of determination tests, and quality index tests. Findings: The findings suggest that there is a significant influence between influencers and interactivity and credibility. Credibility and kindness also have a significant effect on consumer welfare. However, this research cannot prove a significant relationship from argument quality to credibility. Additionally, consumer well-being underscores its significant direct influence on purchase intentions Theoretical and Managerial Implications: For academics, future researcher can discuss the influence of argument quality, credibility of influencers and interactivity, kindness to consumer welfare and purchase intentions on different research objects. For practitioners, the findings provide actionable insights for marketers to choose influencers with credibility, kindness and good quality arguments so that they can improve the consumer welfare felt by their customers, due to increase their intention to purchase their products. Research Limitations: The study is limited to a specific geographic region within Batam and a sample size of 200 respondents, which may affect the findings generalizability. Future research should consider broader geographic and sectoral scopes due to validate as well as extend the applicability of this research construct.